MENGENAL DAMPAK DAN SOLUSI DARI PENGGUNAAN MEDIA SOSIAL TERHADAP KESEHATAN MENTAL REMAJA - Vebrianti, Seli; Tania Widyarahmah, Diva; Rostarina Julyanti, Regina; Tasya Nugraha, Ghenia; Lestaria, Nuri; Hidayat, Risky Achmad; Prayoga, Zidhan Muda; Murtajaa, Yaasmiin; Humairah, Mina Kameliya; Hamdan, Ahmad (Jurnal Pengabdian Masyarakat Indonesia, 2024)
In an era of rapid technological development, social media has become an integral part of teenagers' lives. Although social media offers various benefits, such as communication, information exchange, and business opportunities, its uncontrolled use can have the potential to have a negative impact on mental health. This research aims to explore the influence of social media on adolescent mental health, focusing on the phenomena of social comparison, anxiety and depression that often arise due to exposure to idealistic content. Teenagers often feel pressured to meet unrealistic standards, which can worsen their self-confidence, especially in the context of cyberbullying and online harassment. The research was carried out using a descriptive method, through the stages of preparation, implementation, evaluation and determining solutions. The research results show the importance of supervision and guidance for teenagers in using social media. Proposed solutions include limiting time used on social media, increasing interpersonal communication, and spending time with those closest to you to create an environment that supports mental health. With these steps, it is hoped that teenagers can maintain their mental health and face life's challenges better.